2018
DOI: 10.1016/j.bbmt.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Low Rate of Cervical Cancer Screening among Women with Hematologic Malignancies after Stem Cell Transplant

Abstract: Annual cervical cancer screening with Papanicolaou (Pap) and human papillomavirus (HPV) testing after stem cell transplant (SCT) is recommended, but the uptake is unknown. We aimed to determine the prevalence and predictors of cervical cancer screening in patients with hematologic malignancies. We searched MarketScan Commercial Claims database for women who underwent allogeneic or autologous SCT. The primary outcome was cervical cancer screening, defined as procedures or abnormal results for HPV and/or Pap tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…The balance between Treg and Th17 cells reportedly controls the immune response and is an instrumental factor in regulating helper T cell function associated with the Th1/Th2 shift in autoimmune diseases and graft versus host disease [15]. In our previous studies [16], we found imbalances of Th1/Th2 and Th17/Treg cells in patients with UCC or CIN.…”
Section: Introductionmentioning
confidence: 61%
“…The balance between Treg and Th17 cells reportedly controls the immune response and is an instrumental factor in regulating helper T cell function associated with the Th1/Th2 shift in autoimmune diseases and graft versus host disease [15]. In our previous studies [16], we found imbalances of Th1/Th2 and Th17/Treg cells in patients with UCC or CIN.…”
Section: Introductionmentioning
confidence: 61%
“…The balance between Treg and Th17 cells reportedly controls the immune response and is an instrumental factor in regulating helper T cell function associated with the Th1⁄Th2 shift in autoimmune diseases and graft versus host disease [15]. In our previous studies, we found imbalances of Th1/Th2 and Th17/Treg cells in patients with UCC or CIN.…”
Section: Introductionmentioning
confidence: 74%
“…An imbalance among these T cells will either lead to an immune response or its suppression [14]. Women with hematologic malignancies after stem cell transplant have a low rate of cervical cancer screening for the fresh normal T cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of Treg cells are reportedly increased in cancer patients, and their high numbers are associated with poor survival [19,21]. The balance between Treg cell-and Th17 cell-controlled immune response was a key factor in regulating T helper cell function associated with the Th1⁄Th2 shift in autoimmune disease and graft versus host disease [15]. In our pervious study [16], we systematically determined that the proportion of Th2, Th17, and Treg cells in PBMCs and of their related cytokines IL-4, IL-10, IL-17, IL-23, and TGF-βI in the serum were markedly increased in UCC and CIN patients.…”
Section: Discussionmentioning
confidence: 99%